Acidic hydrolysis performance and hydrolyzed lipid characterizations of wet Spirulina platensis - Nuapon Duongbia (2019)
© 2018, Springer-Verlag GmbH Germany, part of Springer Nature. Acidic hydrolysis process of wet microalgae is a worthy technique to reduce the processes and energy of the production. To aim the alternative fuel as a biofuel feedstock from wet microalgae, the Spirulina platensis containing high moisture, 88–95 wt%, was representative in this research. Microalgae cell disruption by acidic hydrolysis was investigated using various concentrations of sulfuric acid with the hydrolysis temperature in the range of 25–100 °C and hydrolysis time in the range of 30–120 min. The acid-hydrolyzed lipid was extracted from the mixture by solvent extraction using n-hexane. The maximum lipid concentration from acidic hydrolysis was 17.15 wt% that obtained at hydrolysis temperature of 100 °C for 60 min and then extracted with 700 mL of hexane for 30 min. The physical and chemical analyses of the lipid and microalgae solid residue were examined. According to the research results, the higher heating values of hydrolyzed lipid were found in the range of 32–40 MJ/kg and their main chemical components were hexadecane, heptadecane, and palmitic acid. The boiling point ranges of the hydrolyzed lipid were mainly indicated in the fractions of light and heavy gas oils which may be generated in term of biofuel feedstock for automobile fuels.